The art of the turnaround : creating and maintaining healthy arts organizations - Kaiser, Michael M., 1953- (Brandeis University Press, 2008)
This title provides practical advice for fixing troubled arts organizations. Many arts organizations find themselves in financial difficulties because of economic constraints inherent in the industry. Here the author shares his ten basic rules for bringing financially distressed arts organizations back to life.